The abolition of intermarriage in Ezra 10 and the ethnic identity of the postexilic Judean community : a hermeneutic study - Paulo, Bonifacio (Stellenbosch : Stellenbosch University, 2015)
Thesis (MTh)--Stellenbosch University, 2014.